Overcoming online learning challenges in the COVID-19 pandemic by user-friendly platform - Imam Makruf; Endah Tejaningsih (Journal of Education and Learning (EduLearn), 2023)
The shift of learning activities from face-to-face classroom interaction to online learning beyond the classroom due to the global pandemic has caused technological anxiety in teaching and learning. This study analyzed strategies to overcome learning challenges in the COVID-19 pandemic with user-friendly platforms. This study was in the State Institute of Islamic Studies (IAIN) Surakarta, Indonesia, involving 469 lecturers who taught 983 classes as the respondents. The required data were collected using a web-based questionnaire using Google Forms. The data were analyzed descriptively in percentages and elaborated using focus group discussion. The data analysis showed that most teachers used WhatsApp group to overcome learning obstacles during the COVID-19 pandemic. Among the considerations are the lack of information technology infrastructure, the lack of e-learning platforms, the lack of time to adapt, and the difficulty of internet access in some regions. This study contributes to the strategy performed by the lecturers to deal with these challenges is selecting a user-friendly and affordable platform for learning.